Sistem Informasi Manajemen Proyek Berbasis Web Pendataan Suku Cadang Sepeda Motor - Rizki Prasetya Hidayat Nst; Yahfizham (Journal Of Informatics And Busisnes, 2024)
In the ever-evolving digital era, data and information management is becoming increasingly crucial to the success of businesses, including the automotive industry which faces major challenges in managing spare parts inventory. Efficiency in data collection and parts management is critical to ensure the availability of the right parts at the right time, reduce downtime, and improve customer satisfaction. This article introduces a Web-based Project Management Information System for Motorcycle Parts Logging as an innovative solution to meet these needs. The system is designed to facilitate the process of collecting spare parts data from procurement, storage, to distribution. By utilizing web-based technology, this system offers wider accessibility, facilitates real-time monitoring, and allows integration with various other systems.This research uses the waterfall method which includes the stages of requirements analysis, system design, implementation, and testing. The system consists of two main layers: Presentation Layer and Data Layer. The implementation results show that this system can meet the needs of end users, such as automotive workshops and companies, in terms of data collection and management of spare parts. System testing shows that the system works according to the specified specifications. This article also discusses the benefits and advantages that can be obtained from implementing this system, challenges that may be faced during the implementation process, as well as the potential for further development. With this system, it is hoped that the automotive industry can improve operational efficiency and provide better service to customers.